Land use and land cover in the semi-arid region of Sergipe, Brazil - Lima, Luana Brito; Fernandes, Milton Marques (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
In the present study, the land use and cover mapping and the calculation of the landscape ecology metrics of the Jacaré-Curituba settlement, located in the northwest of Sergipe, were carried out. For the mapping, an image from the Gaofen-2 satellite (high spatial resolution) from 2018 was used, which allowed us to obtain eight classes of land use and cover. Landscape ecology was carried out using Fragstat software on forest fragments. The result showed that the Jacaré-Curituba settlement presents its forest cover well preserved, however the small and medium class fragments are fragmented. The classification of the satellite image, carried out in the Qgis 3.4 software, showed that at least 30% of the Permanent Preservation Areas (APP) are anthropized despite the reforestation projects that are carried out in the settlement. It was also identified that anthropic agriculture activity corresponds to the main use of land and coverage of the area; the pastures are lower than those observed in the semi-arid region, which may have been induced by the prohibition of the practice of livestock in this settlement. In this context, it was evidenced that the implementation of the Jacaré-Curituba settlement in this area allowed for more sustainable agricultural production and greater protection of the remnants of the Caatinga forest.